Public Clonotypes and Convergent Recombination Characterize the Naïve CD8+ T-Cell Receptor Repertoire of Extremely Preterm Neonates - Carey, Alison J.; Hope, Jennifer L.; Mueller, Yvonne M.; Fike, Adam J.; Kumova, Ogan K.; van Zessen, David B. H.; Steegers, Eric A. P.; van der Burg, Mirjam; Katsikis, Peter D. (Frontiers in Immunology, 2017)
Respiratory support improvements have aided survival of premature neonates, but infection susceptibility remains a predominant problem. We previously reported that neonatal mice have a rapidly evolving T-cell receptor (TCR) repertoire that impairs CD8+ T cell immunity. To understand the impact of prematurity on the human CD8+ TCR repertoire, we performed next-generation sequencing of the complementarity-determining region 3 (CDR3) from the rearranged TCR variable beta (Vβ) in sorted, naïve CD8+ T cells from extremely preterm neonates (23–27 weeks gestation), term neonates (37–41 weeks gestation), children (16–56 months), and adults (25–50 years old). Strikingly, preterm neonates had an increased frequency of public clonotypes shared between unrelated individuals. Public clonotypes identified in preterm infants were encoded by germline gene sequences, and some of these clonotypes persisted into adulthood. The preterm neonatal naïve CD8+ TCR repertoire exhibited convergent recombination, characterized by different nucleotide sequences encoding the same amino acid CDR3 sequence. As determined by Pielou’s evenness and iChao1 metrics, extremely preterm neonates have less clonality, and a much lower bound for the number of unique TCR within an individual preterm neonate, which indicates a less rich and diverse repertoire, as compared to term neonates, children, and adults. This suggests that T cell selection in the preterm neonate may be less stringent or different. Our analysis is the first to compare the TCR repertoire of naïve CD8+ T cells between viable preterm neonates and term neonates. We find preterm neonates have a repertoire immaturity which potentially contributes to their increased infection susceptibility. A developmentally regulated, evenly distributed repertoire in preterm neonates may lead to the inclusion of public TCR CDR3β sequences that overlap between unrelated individuals in the preterm repertoire.